Agriculture support services in Malawi: Direct effects, complementarities, and time dynamics - Ambler, Kate; de Brauw, Alan; Godlonton, Susan (International Food Policy Research Institute, 2018)
Using a randomized controlled trial, we examine the impacts of cash and input transfers, and a cross-randomized program of intensive agricultural extension over two years. We find large effects on the total value of agricultural production from the transfers (both cash and inputs) in both years. Gains to production are driven by an increase in resources allocated to inputs, specifically pesticides (in the first year) and casual labor (both years). We see no direct evidence that intensive extension is more effective than lead farmer extension support after one year. However, we do find evidence of production gains attributable to intensive extension in the subsequent year, highlighting important time dynamics. In the first year, farmers experience the best outcomes when they receive both transfers and extension, though that pattern is less clear in year 2.